Hem1 inborn errors of immunity: waving goodbye to coordinated immunity in mice and humans - Christodoulou, Alexandra; Tsai, Julia Y.; Suwankitwat, Nutthakarn; Anderson, Andreas; Iritani, Brian M. (Frontiers in Immunology, 2024)
Inborn errors of immunity (IEI) are a group of diseases in humans that typically present as increased susceptibility to infections, autoimmunity, hyperinflammation, allergy, and in some cases malignancy. Among newly identified genes linked to IEIs include 3 independent reports of 9 individuals from 7 independent kindreds with severe primary immunodeficiency disease (PID) and autoimmunity due to loss-of-function mutations in the NCKAP1L gene encoding Hematopoietic protein 1 (HEM1). HEM1 is a hematopoietic cell specific component of the WASp family verprolin homologous (WAVE) regulatory complex (WRC), which acts downstream of multiple immune receptors to stimulate actin nucleation and polymerization of filamentous actin (F-actin). The polymerization and branching of F-actin is critical for creating force-generating cytoskeletal structures which drive most active cellular processes including migration, adhesion, immune synapse formation, and phagocytosis. Branched actin networks at the cell cortex have also been implicated in acting as a barrier to regulate inappropriate vesicle (e.g.cytokine) secretion and spontaneous antigen receptor crosslinking. Given the importance of the actin cytoskeleton in most or all hematopoietic cells, it is not surprising that HEM deficient children present with a complex clinical picture that involves overlapping features of immunodeficiency and autoimmunity. In this review, we will provide an overview of what is known about the molecular and cellular functions of HEM1 and the WRC in immune and other cells. We will describe the common clinicopathological features and immunophenotypes of HEM1 deficiency in humans and provide detailed comparative descriptions of what has been learned about Hem1 disruption using constitutive and immune cell-specific mouse knockout models. Finally, we discuss future perspectives and important areas for investigation regarding HEM1 and the WRC.